The benefits of an Emerging markets over weighted portfolio versus a globally diversified one - De la Torre-Torres, Oscar Valdemar; Aguilasocho-Montoya, Dora; Galeana-Figueroa, Evaristo (Mercados y Negocios, 2020)
In the present paper we test the benefit of overweighting a Global stock portfolio in Emerging markets. This, against a globally full-diversified one. By using a Gaussian two-regime Markov-Switching model in the S&P BMI global, the U.S. S&P 500; the LATAM S&P, the East Europe S&P, the S&P Asia-Pacific, the S&P mid-west and Africa and the S&P BRIC indexes, we tested the benefit of global diversification. From a U.S. dollar based investor perspective, we found in our results that is preferable to invest in a portfolio with only U.S. and Emerging markets stocks, instead of a global broad diversified portfolio. By the fact that a less diversified portfolio has a better mean-variance efficiency in a global diversification context, this result seems challenge the main assumptions of the classical portfolio theory.